An experimental/numerical investigation of the role of the quarl in enhancing the blowout limits of swirl-stabilized turbulent non-premixed flames. (15th January 2019) - Elbaz, A.M.; Yu, S.; Liu, X.; Bai, X.S.; Khesho, I.; Roberts, W.L.
Highlights: The blowout limits of non-premixed swirl flames were measured with and without quarl. An integrated study combining OH-PLIF/PIV measurements and LES are then used to interpret the flame stabilization mechanism. The addition of a quarl significantly enhances the flame blowout limits. The existence of the quarl triggering a larger scale of reversal flow, penetrating deeply upstream into the quarl. A wider range of burnable mixture along the axis in the quarl flames is observed. Abstract: The blowout limits of methane/air non-premixed swirl-stabilized flames were measured with and without quarl. The addition of a quarl significantly enhances the flame blowout limits. The transition from attached flame to blowout was mapped. To explore the role of the quarl, a series of OH-PLIF/PIV experiments, coupled with large eddy simulations (LES) using a transported probability density function (PDF) model, were carried out on flames with and without quarl over a wide range of fuel jet velocity, Uf . The results show that the mean flow field is characterized by two recirculation zones. The existence of the quarl enhances this flow field by triggering a larger scale of reversal flow, penetrating deeply upstream into the quarl. This results in much earlier fuel, extending down into the air tube, where a diffusion flame is stabilized around the stoichiometric mixture contour and locally low scalar dissipation rates. The relative delay in fuel/air mixing in non-quarl flames results in a locally strong scalar dissipation rate layer overlapping the stoichiometric mixture contour, and thus, the flame is highly sensitive to local extinction with increasing fuel jet velocity. At high Uf, in the liftoff flame region, the existence of the quarl enhances the jet spreading and a weak recirculation zone around the highly strained jet is observed. Together with fuel jet spreading, partial oxidization of the mixture upstream the lifted flame base creates a wider range of burnable mixture along the axis in the quarl flames. On the contrary, the high scalar dissipation rate and the absence of a recirculation region in the proximity of the fuel nozzle in the non-quarl flame give rise to an earlier blowout.